GENDER DIFFERENCES AND PRO-SOCIAL TENDENCIES AS PREDICTORS OF SPORTS STRESS MANAGEMENT IN ADOLESCENTS - Eze, Nnabuife Chisom Amarachi; Nweke, Prince Chukwudi; Nwachukwu, Ifeanyi Chukwuma; Ezeani, Obinna Chukwuma (Ayden International Journal of Education and Social sciences, 2025)
This study examined prosocial behaviour and gender as predictors of coping with sports stress among adolescents. Participants were six hundred and forty (640) adolescent athletes in Ebonyi State, Nigerian comprising two hundred and forty (240) males and t wo hundred (200) females. Their ages ranged between 12 to 17 years with a mean age of 14.06 years (SD = 4.79). Cross sectional design was adopted. Two instruments were used for data collection. Result of a Hierarchical Multiple Regression analysis showed that pro-social was a significant predictor of adaptive coping strategy with adolescents’ sports stress(β = 2.02, t = 1.12, p< 05); but it did not predict maladaptive coping. Pro-social behaviour team (β = 1.43, t = 1.15, p< 05) was a significant predictor of adaptive coping strategy with adolescent’s sports stress. Both Prosocial behaviour team and prosocial behaviour opponent were not predictors of maladaptive coping. Gender did not significantly predict adaptive coping strategy with adolescent’s sports stres s; but it significantly predicted maladaptive coping strategy with adolescent’s sports stress (β= -.09, t= -2.22 , p<.05).Implications for the study were stated and suggestions made for further studies.